2009
DOI: 10.1088/0953-8984/21/20/206004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic states of transition metal impurities in silicon carbide

Abstract: Electronic properties of 3C silicon carbide with substitutional transition metal impurities are calculated using an ab initio full-potential linearized augmented plane wave technique. It is shown that transition metal atoms in an SiC host may exist in both magnetic and nonmagnetic states. For different impurity species, the transition from the nonmagnetic to the magnetic state and the corresponding change of the atomic magnetic moments may take place either gradually as the volume of the unit cell changes or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
2
12
3
Order By: Relevance
“…It has been shown that Fe diluted in the SiC matrix is either in interstitial sites or in Si substitution sites (only, and not in C substitution sites) 9,23,24 where it is then ferromagnetic 24 or ferromagnetic and paramagnetic. 9,22 The paramagnetic Fs component is then represented by a singlet [denoted by Fs (para)] and the ferromagnetic Fs component by a sextet [denoted by Fs (ferro)]. The sum of the Fei (C) and Fs (para) components corresponds to a part of the totality of the paramagnetic component of the M€ ossbauer spectra.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that Fe diluted in the SiC matrix is either in interstitial sites or in Si substitution sites (only, and not in C substitution sites) 9,23,24 where it is then ferromagnetic 24 or ferromagnetic and paramagnetic. 9,22 The paramagnetic Fs component is then represented by a singlet [denoted by Fs (para)] and the ferromagnetic Fs component by a sextet [denoted by Fs (ferro)]. The sum of the Fei (C) and Fs (para) components corresponds to a part of the totality of the paramagnetic component of the M€ ossbauer spectra.…”
Section: Resultsmentioning
confidence: 99%
“…This inference should be reasonable since transition metals in SiC were expected to be deep donors or acceptors. 12 The bottom inset of Fig. 4 shows the hysteresis loops at 80 and 300 K. Clear hysteresis loops were observed, which was typical features of FM behavior.…”
mentioning
confidence: 81%
“…Our calculations also show that the substitutional structure of the Fe-doped SiC is nonmagnetic, in good agreement with previous results. 23 However, under Si-rich conditions as for other late 3d TMs, the dimer structure is the most stable one in the Fe-doped SiC. The total and partial DOS for the Fe-doped SiC in the dimer structure is shown in Figure 5.…”
Section: E Form ) E(sic:tm) -E(sic)mµ(tm) + Nµ(si)mentioning
confidence: 92%
“…Moreover, substitutional and interstitial Co atoms do not have a local magnetic moment, i.e., the Co-doped SiC is nonmagnetic. Previous studies of Miao et al 19 and Los et al 23 considered only a substitutional site for the Co-doped SiC which is also nonmagnetic. One may then claim that the Co-doped SiC is always a nonmagnetic system.…”
Section: E Form ) E(sic:tm) -E(sic)mµ(tm) + Nµ(si)mentioning
confidence: 99%